Applicability of belief measures for advertising to sponsorship in sport. Issue 2 (30th April 2020) - Pyun, Do Young; Cho, Heetae; Leng, Ho Keat
Abstract : Purpose: While advertising and sponsorship are conceptually different, many studies have used the same measures for both constructs. The assumption is that respondents perceive both domains similarly. The purpose of this study was to test the invariance of the belief measures between the advertising and sponsorship measurement models across different consumer segments and to provide empirical justification for the practice. Design/methodology/approach: Two independent samples were recruited from two different consumer segments: university student consumers ( n  = 290) and general consumers ( n  = 324). This study conducted multigroup invariance tests using LISREL 8.80. The measurement and structural invariances were concerned with factor loadings ( λ ), factor variance and covariance ( f ) and error variance ( θ ) metrics. Findings: The factor patterns of the belief model were generally invariant between the advertising and sponsorship models in both consumer groups. However, the respondents interpreted three items between advertising and sponsorship in different ways: one annoyance/irritation item in the generic consumer group and two falsity/no sense items in the student consumer groups. Originality/value: While the invariance test reveals three problematic items, the majority of items seem to be invariant, concluding that the advertising belief scale could be applicable to the sponsorship context.